Synthesis of metal–organic coordination polymers and their derived nanostructures for organic dye removal and analyte detection. Issue 4 (August 2022) - Liu, Yu; Yang, Ai-Ai; Zhang, Xiao-Sa; Sun, Ze-Bang; Li, Wen-Ze; Wang, Yan; Luan, Jian; Liu, Hai-Chao
Abstract: Five metal–organic coordination polymers (MOCPs) based on the isonicotinic acid (HIA), namely [M(IA)2 (H2 O)4 ] (M-CP, M = Co, Ni, Cu, Zn, Cd), have been hydrothermally synthesized and structurally characterized. All of the five MOCPs possess similar structures, which are further linked via hydrogen-bonding interactions to generate 3D supramolecular frameworks. The effects of the central metals on the properties of M-CPs have been discussed. Moreover, in order to improve the organic dye removal and analyte detection properties, five nanostructures were synthesized by the pyrolysis method from the five MOCP precursors. The selective organic dye removal and analyte detection properties by the M-CPs and their derivatives (M@C, M = Co, Ni, Cu, Zn, Cd) in the aqueous phase were also comparatively investigated and shown that the highest photocatalytic degradation rates were 98.95% and 92.29% for GV and CR, respectively, in solutions containing Co@C after 4 h. In addition, Co@C, Ni@C and Cu@C show stable catalytic efficiencies after five reaction cycles. Zn/Cd-based CPs and their derived nanostructures can selectively recognize Fe 3+, Cr2 O7 2-, CrO4 2-, MnO4 -, NM and NB. Graphical Abstract: Five MOCPs and their derived nanostructures have been synthesized and characterized. The selective organic dye removal and analyte detection properties are investigated in detail. ga1 Highlights: Five MOCPs based on isonicotinic acid have been synthesized and characterized. Five nanostructures were synthesized via pyrolysis method from the MOCPs. Co/Ni/Cu@C composites exhibit improved dye removal capabilities than MOCPs. Zn/Cd-CPs and Zn/Cd@C composites can be employed as fluorescence sensors. The selective dye removal and analyte detection properties are investigated.